2021
DOI: 10.1007/s40299-021-00551-3
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Leaders’ Emotions Mirror Teacher Professionalism via Collegial Trust

Abstract: The current study explores teacher leaders' emotions and its relationship with teacher professionalism and collegial trust in the Chinese context. A sample of 477 teacher leaders in China responded to three measures, namely, teacher leader emotions, teacher professionalism and trust in colleagues. To analyse the data, confirmatory factor analysis and structural equation modelling were utilised. The results confirmed three hypotheses on the relationships between three constructs. Specifically, positive emotions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
7
0
1
Order By: Relevance
“…The findings indicated that teachers reported a relatively higher level of positive emotions and a lower level of negative emotions. Likewise, one study by Cheng et al (2021) examined positive (e.g. enjoyment, pride and love) and negative emotions (e.g.…”
Section: Emotional Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that teachers reported a relatively higher level of positive emotions and a lower level of negative emotions. Likewise, one study by Cheng et al (2021) examined positive (e.g. enjoyment, pride and love) and negative emotions (e.g.…”
Section: Emotional Well-beingmentioning
confidence: 99%
“…Therefore, the organisational atmosphere is imperative for middle leaders. However, there is not much about the well-being and performance of middle leaders and even less research to understand the influence of their working conditions on these two aspects (Cheng et al, 2021). The situation in the ECE context is rarer and even more dire in the ECE context and in China.…”
Section: Research Contextmentioning
confidence: 99%
“…Teacher leadership is not necessarily about power, but about teachers extending their presence beyond the classroom by seeking additional challenges and growth opportunities, and sharing best practices, working with students (Stein, 2020) within the learning co-creation. Teacher leadership divides the work of teaching into four categoriescollaborating, advocating, modelling, and providing resources (Cheung et al, 2018).…”
Section: Relationship Between Teacher Leadership and Learning Co-crea...mentioning
confidence: 99%
“…Whether a teacher-leader is leading formally or informally, s/he influences and contributes to improving teaching and learning, while performing various roles (Uribe-Flórez et al, 2015). Scholars provide research-based evidence on conditions that enhance teacher-leadership at school: maintenance of respect to teachers and mutual respect at school (Miller et al, 2008), supporting teacher authority at school (Esmaeili et al, 2015), trusting teacher competence (Nguyen et al, 2020), maintenance of positive socio-emotional climate in school (Cherkowski, 2018;Cheng et al, 2021), encouraging teachers to take responsibility for the quality of student learning (Consenza, 2015;Tschannen-Moran, Gareis, 2015), school potential to support teacher leadership (Henderson, 2008;Wieczorek, Lear, 2018), leadership values (Frost, 2008;Killion et al, 2016;Suhaila et al, 2018), leadership skills (Harrison, Killion, 2007;DeHart, 2011;Angelle, DeHart, 2016), school culture (Yusof et al, 2016;Turan, Bektas, 2013;Morris et al, 2019), school improvement (Moore-Steward, Whitney, 2000;Murphy, 2005;Smylie et al, 2005), working with others (York- Barr, Duke, 2004), leadership initiatives (Katzenmyere, Moller, 2001), teacherstudent learning co-creation (Bergmark, Westman, 2014;Bovill et al, 2016;Bovill, 2019a, Bovill, 2019bPotkin, 2019;Resh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The final paper by Cheng et al, (2021) investigated teacher leaders' emotions and their relationship with teacher professionalism and collegial trust using a sample of 477 teacher leaders from primary and secondary schools in China. This study found that positive emotions (e.g.…”
mentioning
confidence: 99%